Implementation of Stock Opname In Collection Development In Special Libraries - Nuriwati, Titan; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
The Ministry of Foreign Affairs library has a diverse collection, ranging from books, journals, magazines, to electronic documents. The collection covers various fields, such as foreign relations, politics, economics, law and culture.One way to care for or maintain a collection is to do it Stock Recording. To find out how librarians carry out Stock Taking activities in Collection Development at the Diplomacy Library of the Ministry of Foreign Affairs Republic of Indonesia. The method used is a qualitative method with a descriptive approach. Based on these results, it can be concluded that the Ministry of Foreign Affairs Library has a fairly complete and diverse collection. The procedure for developing the Diplomacy Library collection at the Ministry of Foreign Affairs is prepared systematically and planned to ensure that the library collection is always relevant to the needs of users. Stock taking of the Diplomacy Library of the Ministry of Foreign Affairs is usually carried out in December or January. Stock taking is carried out by a team consisting of librarians, library supervisors and student interns. The results of the stock take are then recorded in the stock take report. The suggestions that researchers give to the Ministry of Foreign Affairs Library are expected to improve and develop the collection. By improving quality, adding new collections and increasing collection accessibility, it is hoped that the Ministry of Foreign Affairs Library can become a better library and can meet the needs of its users.